Dibenzyltellrium(IV) Diiodide Complexes with N4 Donor Aromatic Schiff Base Ligands - Srivastava, Shekhar; Singh, Deepa (Asian Journal of Chemistry, 2010)
Four complexes of Te(IV) of the type [R2TeSB]2 (whereas R = C6H5CH2, SB = tetradentate Schiff base ligands) have been synthesised and characterised on the basis elemental analysis, molar conductance, IR and X-ray photoelectron data.